NAMA-NAMA SURAT AL-QUR’AN DALAM LUKISAN KALIGRAFI - MITRA HANNI BORU NASUTION, Drs. Syafei, M.Ag, Drs. Erwin, M.Sn (Serupa The Journal of Art Education, 2014)
The purpose of this is project was to describe the names of letters in Al-Qur’an. The respective letter has its own meaning intended to glorify the majesty of Allah in the creation of the universe. Al- Qur’an is the source of science related. To everything acquainted with a few ones. This project intended to familiarize people to the letters names, understand the meaning of each name, and practice and the meaning contained daily life. The theme of this project was “The Names of Letters in Al-Qur’an in the Calligraphy Painting”. The names of letters painted in the calligraphy were Al-fatihah (opening), Ar-Ra’adu (thunder), An-Nur (light), Al-Qamar (the moon), An-Najm (stars), Al-Fajr (dawn), As-Syams (the sun), Al-Ashr (time), Al-Lail (night), and Ad-Dhuha (morning).Keyword: Al Qur'an's letter names, calligraphy